Il problema dell’ontologia del diritto tra vocazione al sistema e razionalitá teleologica (Itinera, 2015)
This paper aims to address the problem of the ontology of law investigating the foundation of the systematic nature that belongs to it as a legal system bearer of an “order”. For this purpose, taking in a comparative consideration three different models, the positivism, the axiological-constitutional one and the classical-metaphysical one, subjects such as the person, the teleological rationality and the natural law are analyzed and discussed in their foundational value and in their specific function.